Validity of a 2-item screening tool to identify families at risk for food insecurity in Brazil - Ana Poblacion; Ana Maria Segall-Corrêa; John Cook; Jose Augusto de Aguiar Carrazedo Taddei (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
This manuscript aimed to develop a brief 2-item screening tool to identify Brazilian households that include families with children at risk for food insecurity. Psychometric analyses including sensitivity, specificity, positive and negative predictive value, accuracy, and ROC curves were used to test combinations of questions to determine the most effective screener to assess households at risk for food insecurity when compared to a gold standard scale. Participants included Brazilian National Survey of Demography and Health on Women and Children (PNDS) surveyed households with a valid Brazilian Food Insecurity Scale (EBIA) response. The sample included 3,920 households representing 11,779,686 households when expanded using PNDS sample weights. With overall prevalence of food insecurity at 21%, a Brazilian 2-item food-insecurity screen showed sensitivity of 79.31%, specificity of 92.95%, positive predictive value of 74.62%, negative predictive value of 94.5% and ROC area 86.13%. This screen also presented high convergent validity for children's nutrition and health variables when compared with the gold standard, the EBIA full scale. Based on its ability to detect households at risk for food insecurity, a 2-item screening tool is recommended for widespread adoption as a screening measure throughout Brazil, especially when rapid decision-making has been made fundamental, as under the COVID-19 pandemic. This screener can enable providers to accurately identify families at risk for food insecurity and promptly intervene to prevent or ameliorate adverse health and developmental consequences associated with food insecurity and swiftly respond to crises.